1982
DOI: 10.1111/j.1346-8138.1982.tb01086.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mosquito Hypersensitivity Terminating as Malignant Histiocytosis

Abstract: A patient with a 5 year history of hypersensitivity to mosquitoes developed a skin nodule on the chest, high fever, and hepatosplenomegaly. The diagnosis of malignant histiocytosis was made, based upon histological examination of the skin and cytological study of the pleural effusion. Immunological studies revealed the impaired activity of both T and B cells. After four weeks of no response to chemotherapy, the patient died. Autopsy revealed malignant histiocytes invading the bone marrow, liver, spleen, lung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Death from malignancy, including malignant histiocytosis and lymphoma, may be based on some form of congenital immunodeficiency. There are several reports suggesting that natural killer cell lymphocytosis may have some relationship to this type of hypersensitivity and to prolonged infection of the EB virus, resulting in malignant histiocytosis (6,8,10). To reach a definite conclusion, however, further immunological studies need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death from malignancy, including malignant histiocytosis and lymphoma, may be based on some form of congenital immunodeficiency. There are several reports suggesting that natural killer cell lymphocytosis may have some relationship to this type of hypersensitivity and to prolonged infection of the EB virus, resulting in malignant histiocytosis (6,8,10). To reach a definite conclusion, however, further immunological studies need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these common reactions, single mosquito bites have produced, in some cases, very severe reactions with systemic symptoms such as high fever, lymphoadenopathy, and hepatosplenomegaly (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, they may exhibit severe, delayed bite reactions which can appear before the malignancy has been diagnosed [14]. Recently, Japanese investigators focused attention on severe, Arthus-type mosquito hypersensitivity appearing in childhood and cLilm.inating, in many cases, in malignant histiocytosis [12,15]. Interestingly, altered cutaneous reactions to mosquito bites have also been reported in three patients with AIDS, after receiving zidovudine treatment [16].…”
Section: Abnormal Bite Reactionsmentioning
confidence: 99%
“…In 15 of these 19 patients, there was evidence of associated viral infections, including Epstein-Barr virus, adenovirus, cytomegalovirus, herpes simplex and varicella-zoster viruses. Mohri et al (14) reported a lO-year-old girl with recurrent bullae after mosquito bites. An intradermal test was positive against an extract from Culex triaeniorhynchus.…”
Section: Discussionmentioning
confidence: 99%